Problematika dan Upaya Menciptakan Lingkungan Bahasa di Madrasah Tsanawiyah - Fitriani, Robiatul; Iswandi, Irvan; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2024)
Private schools such as Islamic boarding schools are described as schools where students study the Al-Qur'an by studying Arabic, because before studying the Al-Qur'an, students are expected to be able to understand Arabic letters and how to pronounce them. This is in line with the stereotype that has developed in society that Islamic boarding school graduates have good Arabic language skills. However, in reality, many students who attend Islamic boarding schools or some who have graduated have not yet actively communicated using Arabic. In one study, this was caused by students not practicing enough Arabic language learning during school. The aim of this research is to analyze and determine the problems experienced by students in applying the language environment and the various efforts of teachers in meeting students' needs in applying the language environment, especially in the school environment. This research method uses a qualitative approach with descriptive techniques. Data collection used observation techniques and in-depth interviews with students and Arabic language teachers at Madrasah Tsanawiyah Ma'had Al-Zaytun, with a total of 42 informants. The results of this research show that the majority of students when interviewed used Arabic, they were able to answer simple questions about greeting and identity, a small percentage were unable to answer simple questions due to a lack of vocabulary, this is one of the problems experienced by students at Madrasah Tsanawiyah Ma'had Al-Zaytun.